Caveolin 3, Flotillin 1 and Influenza Virus Hemagglutinin Reside in Distinct Domains on the Sarcolemma of Skeletal Myofibers - Mika Kaakinen; Tuula Kaisto; Paavo Rahkila; Kalervo Metsikkö (Biochemistry Research International)
We examined the distribution of selected raft proteins on the sarcolemma of skeletal myofibers and the role of cholesterol environment in the distribution. Immunofluorescence staining showed that flotillin-1 and influenza hemagglutinin exhibited rafts that located in the domains deficient of the dystrophin glycoprotein complex, but the distribution patterns of the two proteins were different. Cholesterol depletion from the sarcolemma by means of methyl-β-cyclodextrin resulted in distorted caveolar morphology and redistribution of the caveolin 3 protein. Concomitantly, the water permeability of the sarcolemma increased significantly. However, cholesterol depletion did not reshuffle flotillin 1 or hemagglutinin. Furthermore, a hemagglutinin variant that lacked a raft-targeting signals exhibited a similar distribution pattern as the native raft protein. These findings indicate that each raft protein exhibits a strictly defined distribution in the sarcolemma. Only the distribution of caveolin 3 that binds cholesterol was exclusively dependent on cholesterol environment.